The Review of Commercial Relationship among Iran & Azerbaijan With Applied Economical Theories - Zamin, Mousa Rezvani Chaman (Gyan Management Journal, 2009)
After collapse of the Ex-Soviet, tlu number of countries around the Caspian sea has been divided into five which have huge mine resources, oil & gas, auriftrous resources and have developed regional and economicalcommercial association, with other countries. In order to analyze the commercial state of affairs and existing potential of these countries, the criterion of export & import in a gi.ven period can be used. This paper considers the rate of statistics and these countries using a series of statistics and figures of global website. Of course, this article emphasizes on the condition of economical commercial situation of Islamic Republic of Iran and Azerbaijan Republic. Therefore, one of the necessities of development is to decrease the tariff of efcustoms and commercial taxes, pbut there must he an agreement between these two countries regarding r orming the ma,:ket, needs, trans ortation and . etc to integrate with each other nearly.